Kommissionen til bevaring af danske forfatteres manuskripter og breve: Om et kapitel i det 20. århundredes danske arkiv- og litteraturhistorie - Kromann, Thomas Hvid (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2025)
The subject of the article is the Kommissionen til Bevaring af danske Forfatteres Manuskripter og Breve (the Commission for the Preservation of Manuscripts and Letters by Danish Authors), which was set up in 1910. The article shows that this now completely forgotten commission played a significant role in the early phase of a major and fundamental, but little examined, historical development in Denmark in the 20th century, a period when both writers and archival institutions became increasingly aware of the need to preserve so-called ‘literary remains’ (manuscripts, drafts, letters, diaries etc.) for posterity and to establish archives of contemporary writers. The article examines the historical and institutional background of the commission’s work, including its terms of reference, working method, public action, stages of development – and dissolution. The article also maps the constant negotiation that was clearly in question, as it was far from self-evident that letters and manuscripts would be preserved. The work of the commission resulted in several public controversies, inter-institutional rivalries and discord within the walls of the individual archival institutions. In conclusion, the article shows how the commission’s work became a concrete link between, on the one hand, the incorporation of the Collin Manuscript Collection in 1905 and, on the other, the establishment of the Georg Brandes Archive in 1912. The article, which is based on a large amount of – for the most part – previously unused source material, is a contribution to 20th-century Danish library, archival and literary history in terms of both subject matter and methodology. In terms of the latter, the article concludes not only that archives can provide source material, such as liter-ary studies, but also that they can become an object of analysis in their own right: the studies of individual archives’ provenance, structure, discarded material, supplements etc. can be mapped to varying degrees, and they can potentially provide an insight into mechanisms in the literary field.